If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying v + 1 + v + 1 + v + 1 = v * v Reorder the terms: 1 + 1 + 1 + v + v + v = v * v Combine like terms: 1 + 1 = 2 2 + 1 + v + v + v = v * v Combine like terms: 2 + 1 = 3 3 + v + v + v = v * v Combine like terms: v + v = 2v 3 + 2v + v = v * v Combine like terms: 2v + v = 3v 3 + 3v = v * v Multiply v * v 3 + 3v = v2 Solving 3 + 3v = v2 Solving for variable 'v'. Combine like terms: v2 + -1v2 = 0 3 + 3v + -1v2 = 0 Begin completing the square. Divide all terms by -1 the coefficient of the squared term: Divide each side by '-1'. -3 + -3v + v2 = 0 Move the constant term to the right: Add '3' to each side of the equation. -3 + -3v + 3 + v2 = 0 + 3 Reorder the terms: -3 + 3 + -3v + v2 = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -3v + v2 = 0 + 3 -3v + v2 = 0 + 3 Combine like terms: 0 + 3 = 3 -3v + v2 = 3 The v term is -3v. Take half its coefficient (-1.5). Square it (2.25) and add it to both sides. Add '2.25' to each side of the equation. -3v + 2.25 + v2 = 3 + 2.25 Reorder the terms: 2.25 + -3v + v2 = 3 + 2.25 Combine like terms: 3 + 2.25 = 5.25 2.25 + -3v + v2 = 5.25 Factor a perfect square on the left side: (v + -1.5)(v + -1.5) = 5.25 Calculate the square root of the right side: 2.291287847 Break this problem into two subproblems by setting (v + -1.5) equal to 2.291287847 and -2.291287847.Subproblem 1
v + -1.5 = 2.291287847 Simplifying v + -1.5 = 2.291287847 Reorder the terms: -1.5 + v = 2.291287847 Solving -1.5 + v = 2.291287847 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '1.5' to each side of the equation. -1.5 + 1.5 + v = 2.291287847 + 1.5 Combine like terms: -1.5 + 1.5 = 0.0 0.0 + v = 2.291287847 + 1.5 v = 2.291287847 + 1.5 Combine like terms: 2.291287847 + 1.5 = 3.791287847 v = 3.791287847 Simplifying v = 3.791287847Subproblem 2
v + -1.5 = -2.291287847 Simplifying v + -1.5 = -2.291287847 Reorder the terms: -1.5 + v = -2.291287847 Solving -1.5 + v = -2.291287847 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '1.5' to each side of the equation. -1.5 + 1.5 + v = -2.291287847 + 1.5 Combine like terms: -1.5 + 1.5 = 0.0 0.0 + v = -2.291287847 + 1.5 v = -2.291287847 + 1.5 Combine like terms: -2.291287847 + 1.5 = -0.791287847 v = -0.791287847 Simplifying v = -0.791287847Solution
The solution to the problem is based on the solutions from the subproblems. v = {3.791287847, -0.791287847}
| 9x+5=6x+17 | | 15z-2=4(2z+3) | | 8x-23=73 | | 4x+4=24 | | 4x^2-28x+45=0 | | 10x+7=5x+13 | | 4x^2-23+51=5x+6 | | 2x+17=12x-83 | | (3x-7)+x+13=90 | | 6p+14p=140 | | 6p+149=140 | | 3x+5y=-9 | | 9h=9.3 | | 2x+5=-4x+35 | | 6x^2+17x-28=0 | | 6-0.25f=f-3 | | 7n+6=62 | | 5r+14+3r=2r+38 | | 10x-24=6x+4 | | 3n+5=11 | | 4x^2+27x+35=0 | | x^2+4x-19=2x-4 | | x^2+7x-5=3 | | x^2+7x-5=0 | | 2(3x+5)=40 | | 10=3x+12 | | 3.25+0.25x=20 | | 3.25+0.25x=0 | | -8.6x=68.8 | | 3.5+0.25=0 | | 5y+2=7y-8 | | 4a-5=23 |